Technology Acceptance Model: Intention Implementation E-Government System - Abd Rohman Taufiq; M. Iswahyudi (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2024)
This study aimed to examine the effect of perceived usefulness, ease of use on the attitudes and interests of accounting students in using the online learning system (e-learning) with the addition of gender as a moderating variable. E-learning is a system used by educational institutions in Banyuwangi to conduct distance learning, which was initially implemented due to the COVID-19 pandemic, so learning must be done online inevitably. Online learning is something new, which of course for accounting students will be very difficult considering that in accounting requires a lot of understanding of calculations. The research sample was users of e-learning accounting students at universities in Banyuwangi. Data analysis used Partial Least Square with warpPLS version 3.0 software. The results showed that perceived usefulness was a determinant of the attitudes and interests of accounting students in using e-learning, which in turn, the attitudes of users would determine students' interest in using e-learning. This study also proves that perceived ease of use does not affect accounting students' attitudes in using e-learning. In addition, this study also found that gender did not moderate the relationship between perceived ease of use and usefulness of student attitudes in using e-learning.